Analysis of motion and vibration characteristics of elastic composite cylindrical roller bearing. (February 2023) - Zhang, Xiangyun; Bian, Qiang; Chen, Ming; Zhao, Chunjiang; Zeng, Guang; Jiao, Bowen; Liu, Bingyang
To investigate the motion characteristics and vibration characteristics of elastic composite cylindrical roller bearings (ECCRBs), a simulation model of the ECCRB is established in ABAQUS software. The influences of filling degrees and working conditions on motion characteristics of the ECCRB are compared, and the modal characteristics and harmonic response of the ECCRB are analyzed. Calculation results show that when the filling degree increases from 0% to 60%, there is a nonlinear relationship between the filling degree and the slip rate of cage, the natural frequency of each order decreases, and the vibration displacement of ECCRB increases under the excitation load; increasing the rotation speed and decreasing the radial load reasonably is beneficial to the motion stability of the ECCRB. At the same time, with the increase of the excitation load, the vibration displacement of the ECCRB increases. The analysis results can present some theoretical basis for the structural optimization of the ECCRB.